The Perks of Being in the Smaller Team: Incentives in Overlapping Contests - Christoph March; Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate overlapping contests in multi-divisional organizations in which an individual's effort simultaneously determines the outcome of several contests on different hierarchical levels. We show that individuals in smaller units are advantaged in the grand (organization-wide) contest for two reasons: First, the incentive to free-ride is smaller in inter-divisional contests. Second, competition in the intra-divisional contest is less fierce. Both effects induce a higher marginal utility of effort provision. We test the model in a laboratory experiment and confirm its main predictions. Our results have important consequences for the provision of incentives in organizations and the design of sports competitions.
Keywords: C72; C92; D72; 330; contest; rent-seeking; hierarchy; teams; experiment